Atypical Presentation of Shiga Toxin Haemolytic Uremic Syndrome (STEC-HUS) - Inês Marques; Leonor Figueiredo; Isabel Pataca; Gabriela Pereira; João Estrada; Rute Baeta Baptista (Publicações Ciência e Vida, 2022)
Shiga-toxin producing Escherichia coli (STEC) infection is the most common cause of haemolytic uremic syndrome (HUS) in children. It should be noted that 5% of STEC-HUS patients have no prodromal diarrhoea, while it may be present in up to 30% of atypical HUS (aHUS) cases. In patients at risk for aHUS, STEC infection may act as a trigger rather than playing a causative role. Presently, eculizumab is the first-line therapy for children presenting with aHUS, whereas treatment of children with STEC-HUS is mainly supportive. We report the case of a child with STEC-HUS who had a severe presentation, requiring renal replacement therapy in the acute phase and surgical treatment for a colonic stricture that arose as a late extra-renal complication of the disease. We aim to review the diagnostic workup of children presenting with HUS, stressing the resources available in our setting. In Portugal, O157 E. coli isolation medium is widely available in clinical laboratories. Non-O157 STEC identification requires specific testing, which is increasingly relevant as non-O157 STEC is becoming a more common cause of STEC-HUS than serogroup O157. The National Health Institute Doutor Ricardo Jorge (INSA) has the capacity to identify verotoxin genes and to proceed to verotxin-producing E. coli (VTEC) pathogenicity assessment using multiplex polymerase chain reaction. Fresh stool samples must be obtained early in the disease course to be sent for culture in O157 E. coli isolation medium and for non-O157 E. coli identification assays.